Research on the influence of fertilization on yield and economic efficiency at soya culture - Alina Şimon; Felicia Cheţan; Alin Popa (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The purpose of this paper is to evaluate the soybean yield obtained from the application of the additional fertilization and economic efficiency determination. Experimental factors: Factor A - the fertilization: a1-N20P20K0 (100 kg/ha), applied simultaneously with sowing, a2-N20P20K0 (100 kg/ha), applied simultaneously with the sowing + N20P20K0 (100 kg/ha), applied in the 4-6 leaves phenophase, a3-N20P20K0 (100 kg/ha) applied simultaneously with sowing + N30 (100 kg/ha), applied in the 4-6 leaves phenophase and a4-N20P20K0 (100 kg/ha) applied simultaneously with sowing + N20 (100 kg/ha), applied in the 4-6 leaves phenophase; factor B - soybean varieties: b1-Mæalina TD, b2Darina TD, b3-Felix and b4-Onix; factor C - climatic conditions in the experimental years: c1-2015; c2-2016; c3-2017. By applying additional fertilization are obtained a very significant yields of over 120 kg/ha. The Mæalina soybean variety achieved an average yield of 2706 kg/ha, in the period 2015-2017, with differences significantly higher than the other three varieties studied under the same conditions. The thermal and pluviometric regime is an important factor in determining the yield of a crop, in 2015 was obtained an average yield of 1912 kg/ha, and in the years 2016 and 2017 achieved the yield of 3447 kg/ha respectively 2329 kg/ha, with significantly higher differences than in 2015. The yield of the four varieties is in direct relationship with the level of fertilization.
Keywords: Q01; Q15; Q16; 330; soybean; yield; fertilization; economic efficiency; climatic conditions